Lucian Freud the painter's etchings - Figura, Starr (Museum of Modern Art, 2007)
"One of the foremost artists working today, Lucian Freud had redefined portraiture and the nude through his frank scrutiny of the human form. Although he is best known as a painter, etching is integral to Freud's practice. This volume accompanies a major Museum of Modern Art exhibition presenting the full scope of Freud's etchings, along with a critical selection of related paintings and drawings. Organized by Starr Figura, Lucian Freud: The Painter's Etchings includes seventy etchings - from the artist's rare early experiments of the 1940s to the increasingly complex compositions he has created since rediscovering the medium in the early 1980s - juxtaposed with some twenty-two paintings and seven drawings. Figura's essay in this catalogue examines the dramatic dialogue among mediums in Freud's practice, and explores the crucial cross-pollinating relationship between his etchings and his works on canvas. Pared down to essentials of line, often depicting figures cropped or isolated against empty backgrounds, Freud's prints achieve a startling degree of psychological tension and formal abstraction. Etching is here revealed as a medium uniquely suited to Freud's distinct artistic goals."